EMPLOYEE AND COMPANY ASSETS MONITORING SYSTEM - Aina Faizah, Mohmad (Universiti Malaysia Sarawak (UNIMAS), 2019)
In today’s world,smartphone is an important device in daily life. The aim of thissystem is to monitor the employee activities and productivity in the company compound and to improve the growth of the company’s performance. The system will be built on an Android operating system and will be used in an android smartphone. This system can monitor the employee and company assets in the company compound. By using this system, the employer or toplevel management can easily monitor and track their employee.